A new correlation for hazardous area classification based on experiments and CFD predictions. Issue 1 (7th May 2018) - Souza, Andrey O.; Luiz, Aurelio M.; Neto, Antonio T. P.; Araujo, Antonio C. B.; Silva, Heleno B.; Silva, Sidinei K.; Alves, Jose J. N.
Abstract : A correlation developed by the authors for prediction of hazardous area extension due to fugitive emissions is described in this work. The correlation is based on computational fluid dynamic (CFD) simulation data. The CFD simulation setups were obtained from a Computational Design of Experiments. The CFD model has been validated experimentally. The transport properties, orifice size, temperature, pressure, gas molar mass, and lower explosive limit (LEL) were varied in a range of practical interest using the statistical Technique Latin hypercube to spread the simulation setups. The effect of each variable on hazardous area extension was obtained from the CFD results leading to an analytical correlation for practical use in estimating the extension of the hazardous area. The results showed that the extension of hazardous area in still ambient is merely a function of the leaking gas molar flow rate and gas volume fraction at LEL. The results from the correlation described in this work were compared to results from correlations existing in the literature. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 38: 21–26, 2019